Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1093/jat/17.6.378
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Freezing on the Concentration of Drugs of Abuse in Urine

Abstract: Benzoylecgonine, 11-nor-delta 9-tetrahydrocannabinol-9-carboxylic acid (THC-acid), phencyclidine, codeine, morphine, amphetamine, methamphetamine, and lysergic acid diethylamide were dissolved in urine, stored frozen in plastic tubes at -16 to -18 degrees C, defrosted, transferred to other tubes, and analyzed by gas chromatography/mass spectrometry (GC/MS); no significant loss of compound was observed, except for THC-acid, which showed an average loss of 11%, ranging from 0 to 34% of the total concentration. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…In contrast, a study by Dugan et al found cTHC to be within 25% of the original concentration after 12 months in urine stored at −20°C [7]. Paul et al found a decrease in cTHC after frozen storage for 45 days, but the average decrease was only 11%, ranging as great at 34% [6].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In contrast, a study by Dugan et al found cTHC to be within 25% of the original concentration after 12 months in urine stored at −20°C [7]. Paul et al found a decrease in cTHC after frozen storage for 45 days, but the average decrease was only 11%, ranging as great at 34% [6].…”
Section: Discussionmentioning
confidence: 89%
“…However, there has not been a comprehensive study conducted to determine the stability of medications, metabolites, and illicit substances commonly requested for testing by physicians treating patients with pain and pain-related disorders. See Table 1 for a summary of the extant literature [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…THC-COOH appears to be stable in spiked samples stored in silanised glass at -20°C for long periods of time (Levine and Smith 1990;Paul et al 1993). However, urine is usually collected in plastic containers where an adsorptive loss may occur; also, adsorption on borosilicate glass surfaces has been reported (Paul et al 1993).…”
Section: Stability Of Drugs and Formation Of Artefacts In Postmortem mentioning
confidence: 99%
“…However, urine is usually collected in plastic containers where an adsorptive loss may occur; also, adsorption on borosilicate glass surfaces has been reported (Paul et al 1993). The lower solubility of THC-CCOH in urine decreases at both a lower temperature and higher salt concentration, promoting adsorption on container walls.…”
Section: Stability Of Drugs and Formation Of Artefacts In Postmortem mentioning
confidence: 99%